REINFORCEMENT OF PANCASILA AS A PHILOSOPHY OF REGULATION-MAKING - Lita Tyesta ALW (Diponegoro Law Review, 2020)
The purpose of law is to implement the ideals of order and justice into the interpersonal space of life that is society. Therefore, every legal regulation must abide and be based on norms that exist in society which envisages the modern ordered and just society. The law should be prospective, understandable, clear, fixed and certain. In Indonesia, Pancasila is a set of five principles by which the whole systems of government, law, and social life should be adopted by the nation. However, the current political climate has changed the political reception towards reinforcing Pancasila as the basic philosophy of regulation-making. This conceptual article discussed about how the process of regulation-making should be based on Pancasila as grundnorm, or basic norms of the nation’s life. This article concluded that the elaboration of the grundnorm in the formation of laws and regulations by taking into account the principles of the formation of laws and regulations as well as the principles of material content along with the guidelines and techniques for their formation, so that the formation of laws and regulations fulfills the rules in substance (materially) and formally.